An Islamic Epistemological Perspective on Multiple Intelligences: Implications for Islamic Religious Education - Sarah Dina; Muhammad Chirzin; Marhumah Marhumah; Dede Rohmatul Parid (Civilization Research: Journal of Islamic Studies, 2026)
Research on multiple intelligences has been predominantly developed within psychological theories, particularly Howard Gardner’s framework, while its epistemological foundations from an Islamic perspective have received limited scholarly attention. Previous studies have generally discussed Qur'anic perspectives on human potential or the application of multiple intelligences in education separately, without establishing an integrated epistemological framework that connects Islamic religious education to Qur'anic concepts of knowledge, human nature, and intelligence. To address this gap, this study examines the epistemological foundations of multiple intelligences from the perspective of the Qur’an and explores their implications for IR education. This study employed a qualitative library research approach using descriptive and analytical methods. Data were collected through an analysis of Qur'anic verses, classical and contemporary kafir, and relevant literature on multiple intelligences and Islamic education. The findings demonstrate that the Qur'an conceptualizes intelligence as a holistic human capacity rooted in the integration of 'aql (reason), qalb (heart), sam' (hearing), and baṣar (sight), which collectively serve as epistemological instruments for acquiring, understanding, and internalizing knowledge. Unlike conventional perspectives that primarily emphasize cognitive dimensions, the Qur’anic perspective positions spiritual and moral dimensions as the foundation that integrates various forms of human intelligence. This study contributes an Islamic epistemological framework for understanding multiple intelligences and provides a theoretical basis for developing more holistic, inclusive, and student-centered approaches to IR that accommodate learners’ diverse potentials while strengthening faith, character, and intellectual development.